2011
DOI: 10.1001/jama.2011.991
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Gonadotropin-Releasing Hormone Analogue Triptorelin on the Occurrence of Chemotherapy-Induced Early Menopause in Premenopausal Women With Breast Cancer

Abstract: clinicaltrials.gov Identifier: NCT00311636.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
256
1
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 267 publications
(269 citation statements)
references
References 32 publications
2
256
1
10
Order By: Relevance
“…122 Some studies, including randomized trials, have evaluated the role of menstrual suppression with gonadotropin-releasing hormone (GnRH; also known as LH-releasing hormone [LHRH]) agonists to preserve ovarian function during chemotherapy. [123][124][125][126][127][128][129][130][131] Some meta-analyses have shown that GnRH agonist may be beneficial for fertility preservation. [132][133][134] However, the impact of these meta-analyses are limited by flaws such as only examining women with breast cancer and only including trials that were not adequately powered and did not use blinding and/ or a placebo condition.…”
Section: Options For Femalesmentioning
confidence: 99%
“…122 Some studies, including randomized trials, have evaluated the role of menstrual suppression with gonadotropin-releasing hormone (GnRH; also known as LH-releasing hormone [LHRH]) agonists to preserve ovarian function during chemotherapy. [123][124][125][126][127][128][129][130][131] Some meta-analyses have shown that GnRH agonist may be beneficial for fertility preservation. [132][133][134] However, the impact of these meta-analyses are limited by flaws such as only examining women with breast cancer and only including trials that were not adequately powered and did not use blinding and/ or a placebo condition.…”
Section: Options For Femalesmentioning
confidence: 99%
“…Despite limitations in study design and statistical power, the most recent randomized controlled trials suggest a protective ovarian effect in both HR+ and HR-patients and no signal for harm from a breast cancer recurrence standpoint 76,77 . A recent metaanalysis supports these findings 78 .…”
Section: Gnrh Agonists and Ovarian Function Preservationmentioning
confidence: 99%
“…Gonadal protection through hormonal manipulation with GnRH analogs for FP in women treated with gonadotoxic chemotherapy has demonstrated conflicting results (3,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Published clinical guidelines from clinical associations are variable in their recommendations regarding GnRH analogs.…”
Section: Usefulness Of Gonadotropin-releasing Hormone (Gnrh)mentioning
confidence: 99%